(untitled) (European Journal of Government and Economics, 2026)
Although there are a large number of studies exploring the importance of quality of life (QoL) in cities, there is a significant gap in research linking the impact of urban governance on the QoL of their citizens. Therefore, the objective of this study is to identify and examine how the tools available to local governments have a significant impact on our area of study. Using a systematic mapping review with bibliometric analysis, 139 articles published in the last 10 years, from 2015 to 2025, were analyzed. Governance components such as transparency, e-government, responsiveness, rule of law, citizen participation, accountability, effectiveness and efficiency have been analyzed. The results of this research can help city planners prioritize those factors that have the greatest impact on or are most relevant to citizens’ QoL.